EFFECT OF HCN AND INTERCALED CROPS ON DAMAGE CAUSED BY THE "SMALLPOX BUG" Cyrtomerius bergi Froeschner TO THE YUCCA CULTIVATION - CASTAÑO, OSCAR; BELLOTTI, ANTHONY C.; VARGAS-H., OCTAVIO (Revista Colombiana de Entomología, 1985)
This work was realized by CIAT and the Department of Entomology, Un iversity of Caldas. Two experimental under field were carried out to compare the chemical control of C. bergi with the varietal preference, using the varieties Chirosa-gallinaza (low HCN content) and M Col 1684 (high HCN content) and also to determine the efficiency of crotalaria (Sun hemp) intercropped with cassava compare with cassava. The species of sun hemp used was C. juncea at two plating times: the first at the same time with cassava and the second, six months later. The insecticide used was dimethoate (0.8 grs. of A. I/liter of water), applied every two weeks. In the first trial, the variety chirosa-gallinaza with insecticide had 30°/o root attack whereas without insecticide it was 62.3qo; the variety M Col 1684, both with and without insectincide, presented no root damage. In the second experiment, when cassava was intercropped with crotalaria, there was a 3.7% of root damage, while in the monoculture of cassava it was 61.20/o; nevertheless, in the intercropping there was a yield reduction of 22°/o in cassava. Comparing the cassava treatment with insecticide and the cassava + crotalaria it was found that the latter system was the most effective for controlling this subterranean sucking insect.